2007
DOI: 10.1152/japplphysiol.01374.2006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal differences in the influence of ischemic factors and deformation on the metabolism of engineered skeletal muscle

Abstract: Gawlitta D, Oomens CW, Bader DL, Baaijens FP, Bouten CV. Temporal differences in the influence of ischemic factors and deformation on the metabolism of engineered skeletal muscle. J Appl Physiol 103: 464-473, 2007. First published April 19, 2007 doi:10.1152/japplphysiol.01374.2006.-Prolonged periods of tissue compression may lead to the development of pressure ulcers, some of which may originate in, for example, skeletal muscle tissue and progress underneath intact skin, representing deep tissue injury. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 30 publications
4
74
1
Order By: Relevance
“…It is a powerful technique that is mainly being designated for regenerative medicine in a wide variety of tissues and organs (Bach et al 2003;Mol et al 2005). In particular, tissue engineering of skeletal muscle has many applications, ranging from in vitro model systems for drug-screening (Vandenburgh et al 2008), pressure sores (Gawlitta et al 2007) and physiology to in vivo transplantation to treat muscular dystrophy and muscular defects (Boldrin et al 2008). Obviously, tissue engineering could also be employed for the in vitro production of skeletal muscle tissue from farm animals for consumption purposes (Edelman et al 2005).…”
Section: Culturing Of In Vitro Meatmentioning
confidence: 99%
“…It is a powerful technique that is mainly being designated for regenerative medicine in a wide variety of tissues and organs (Bach et al 2003;Mol et al 2005). In particular, tissue engineering of skeletal muscle has many applications, ranging from in vitro model systems for drug-screening (Vandenburgh et al 2008), pressure sores (Gawlitta et al 2007) and physiology to in vivo transplantation to treat muscular dystrophy and muscular defects (Boldrin et al 2008). Obviously, tissue engineering could also be employed for the in vitro production of skeletal muscle tissue from farm animals for consumption purposes (Edelman et al 2005).…”
Section: Culturing Of In Vitro Meatmentioning
confidence: 99%
“…Specific challenges still exist in supporting growth of sufficient differentiated muscle tissue for regenerative purposes, the capacity to supply sufficient oxygen and nutrients to the core of the construct, the need for these tissue constructs to remain viable and be vascularised and innervated in vivo (Bach et al, 2004;Birla et al, 2005;Davis et al, 2007;Gawlitta et al, 2007). Overcoming these challenges to achieve maximal therapeutic benefits centres largely around the ability to accurately recapitulate the endogenous environment for growth in vitro.…”
Section: Future Applications 61 Three-dimensional Skeletal Muscle Timentioning
confidence: 99%
“…It is tempting to extrapolate this cell deformation data to the clinical setting, where tissue breakdown, in the form of pressure ulcers, may be induced within relatively short periods of continuous loading. In addition, the model has recently been modified to examine the relative temporal influence of cell deformation and hypoxia on tissue engineered skeletal muscle [23]. It utilised a three-dimensional in-vitro system, incorporating cultured muscle cells seeded in an agarose gel construct.…”
Section: Musclementioning
confidence: 99%
“…Results indicated that cell death was evident within 1-2 h at strain values, equivalent to clinically relevant pressures. A further study examined the relative temporal influence on cell deformation and hypoxia on these tissue engineered equivalents [23]. Compression levels at 20 and 40%, affected tissue viability with the first 22 h, as assessed by stains for both cell necrosis and cell apoptosis.…”
Section: Musclementioning
confidence: 99%
See 1 more Smart Citation